Non-Invasive Micro-Test Technology in Plant Physiology Under Abiotic Stress: From Mechanism to Application - Tianpeng Zhang; Peipei Yin; Xinghong Yang; Yunqi Liu; Ruirui Xu (Plants)
Non-invasive Micro-test Technology (NMT) represents a pioneering approach in the study of physiological functions within living organisms. This technology possesses the remarkable capability to monitor the flow rates and three-dimensional movement directions of ions or molecules as they traverse the boundaries of living organisms without sample destruction. The advantages of NMT are multifaceted, encompassing real-time, non-invasive assessment, a wide array of detection indicators, and compatibility with diverse sample types. Consequently, it stands as one of the foremost tools in contemporary plant physiological research. This comprehensive review delves into the applications and research advancements of NMT within the field of plant abiotic stress physiology, including drought, salinity, extreme temperature, nutrient deficiency, ammonium toxicity, acid stress, and heavy metal toxicity. Furthermore, it offers a forward-looking perspective on the potential applications of NMT in plant physiology research, underscoring its unique capacity to monitor the flux dynamics of ions/molecules (e.g., Ca2+, H+, K+, and IAA) in real time, reveal early stress response signatures through micrometer-scale spatial resolution measurements, and elucidate stress adaptation mechanisms by quantifying bidirectional nutrient transport across root–soil interfaces. NMT enhances our understanding of the spatiotemporal patterns governing plant–environment interactions, providing deeper insights into the molecular mechanism of abiotic stress resilience.